PERLINDUNGAN HAK-HAK MASYARAKAT ADAT DALAM HUKUM HAK ASASI MANUSIA INTERNASIONAL (Studi Perbandingan Perlindungan Hak-Hak Tenurial Masyarakat Adat di Indonesia dan Kenya) - Rahmani Fitriah; Zulfikar Jayakusuma; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The existence of human rights and its arrangements is really important because without human rights, human cannot develop their talents and fulfill their needs. In addition to regulating human rights in general, there are also human rights arrangements held for indigenous peoples. Indigenous peoples are communities that live on the basis of ancestral ancestry over a customary territory, which has sovereignty over land and natural resources, socio-cultural life governed by customary law and traditional institutions that manage the sustainability of community life.The purpose of this thesis is to find out how international human rights law protect the rights of indigenous peoples and to find out how the protection of tenure rights of indigenous peoples in Indonesia and the protection of tenure rights of indigenous peoples in Kenya and the comparison of the protection on the both states.From the result of the research it is found that All states include Indonesia and Kenya have an obligation to uphold the rights possessed by indigenous peoples, especially their tenure rights. Even though the state has not ratified UNDRIP, ILO No.169 or does not regulate other regulations on the protection of the rights of the indigenous people, the state still have to protect their people and use any other regulation such as the Universal Declaration of Human Rights, ICCPR, ICESCR, etc as their legal based. The state has the duty to effectively protect the rights held by indigenous peoples as governed by international human rights law, regional regulations of their territories and also its national regulations. It is not permissible for the state to violate the rights possessed by indigenous peoples simply because their identities are different from the people in the country in general, or displace nor relocating them even under the pretext of conservation without their consent